Development of a rapid and sensitive UPLC‐MS/MS assay for the determination of TM‐2 in beagle dog plasma and its application to a pharmacokinetic study. (15th May 2014) - Lin, Hongli; Zhao, Yunli; Men, Lei; Yang, Mingjing; Liu, Hui; Shao, Yanjie; Wang, Pei; Tang, Xing; Yu, Zhiguo
ABSTRACT A simple and sensitive method based on ultra‐high‐performance liquid chromatography–tandem mass spectrometry (UPLC‐MS/MS) has been developed for the determination of TM‐2, which was a novel semi‐synthetic taxane derivative in beagle dog plasma. Cabazitaxel was chosen as internal standard. Following extraction by methyl tert‐butyl ether, the chromatographic separation was achieved on a Thermo Syncronis C18 column (50 × 2.1 mm, 1.7 µm) by gradient elution within a runtime of 3.5 min. The mobile phase consisted of (A) acetonitrile and (B) 2 mmol/L ammonium acetate in water. The detection was accomplished using positive ion electrospray ionization in multiple reaction monitoring mode. The MS/MS ion transitions were monitored at m/z 812.39 → 551.35 for TM‐2 and 836.36 → 555.26 for IS, respectively. The method was linear for TM‐2 (r = 0.9924) ranging from 2.5 to 1000 ng/mL. The intra‐day and inter‐day precisions (relative standard deviation) were within 8.0 and 17.6%, respectively, and the accuracy (relative error) was less than 2.3%. The extraction recovery ranged from 83.1 to 97.1%. The reliable method was successfully applied to a pharmacokinetic study of TM‐2 in beagle dogs after intravenous drip with different doses of 0.6, 1.2, and 2.4 mg/kg, respectively. Copyright © 2014 John Wiley & Sons, Ltd.